Offshoring, Matching, and Wage Inequality: Theory and Evidence - Gueyon Kim; Dohyeon Lee; Dario Pozzoli (Institute of Labor Economics (IZA), 2025)
This paper examines how offshoring affects worker skill demands and studies its implications for wage inequality. Using Danish administrative data, we find that offshoring increases firm-level demand for higher skills in occupations with high exposure to foreign competition. This effect is more pronounced in low-productivity firms, highlighting distributional impacts across firms. By constructing a Becker-type worker-firm matching model in a global economy, we demonstrate underlying mechanisms and quantify the role of offshoring-induced adjustments. Offshoring increases firm similarity in worker skill and wages within high-exposed jobs, leading to a decrease in between-firm inequality—a contrast to the effects of technological change.
Keywords: C78; F14; F16; J24; J31; 330; offshoring; worker-firm matching; segregation by skill; wage inequality; between-firm inequality